EVALUASI PENGOPTIMALAN INSTALASI PENGOLAHAN AIR LIMBAH TERHADAP PENCEMARAN SUNGAI WANGI DI PASURUAN - Mochamad Awaludin Adam; Maftuch . (Journal of Environmental Engineering and Sustainable Technology, 2015)
Water pollution that occurred 2014 in Wangi river flow caused by many things, such as household waste, industrial waste disposal and the market as well as the erosion process. The sourcesed of river stream that comes from the river Prigen and empties into the river flow Bangil Pasuruan. Pollution in rivers Wangi had a negative effect on the environment. Streams that previously could be used by residents for everyday activities began to change in recent times. The activities necessary to manage liquid waste so that the effluent that discharged into the environment does not exceed effluent quality standards have been set. The activity will be successful if any commitment and control as well as the cooperation of all parties.